The quadratic equation x^2 - 3x + 4 = 0 has to be solved.

For a quadratic equation ax^2 + bx + c = 0, the roots are `(-b +sqrt(b^2 - 4ac))/(2a)` and `(-b -sqrt(b^2 - 4ac))/(2a)`

For x^2 - 3x + 4 = 0, the roots are:

x1 = `(3 - sqrt(9 - 16))/2 = (3 - sqrt7*i)/2`

x2 = `(3 + sqrt7*i)/2`

**The roots of the equation x^2 - 3x + 4 = 0 are `(3 - sqrt7*i)/2`
and** `(3 + sqrt7*i)/2`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.